2020
DOI: 10.3991/ijim.v14i11.13903
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Detection of Phishing Websites Using Multilayer Perceptron

Abstract: Phishing is a type of Internet fraud that aims to acquire the credential of users via scamming websites. In this paper, a novel approach is utilized that uses a Neural Network with a multilayer perceptron to detect the scam URL. The proposed system improves the accuracy of the scam detection system as it achieves a high accuracy percentage of 98.5%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 21 publications
(22 reference statements)
0
9
0
Order By: Relevance
“…It consists of three or more layers ( i.e., input and an output layer with one or more hidden layers) of nonlinearlyactivating nodes. This algorithm employs the backpropagation supervised learning method and works through determining the most proper synaptic weight in classifying patterns in the training dataset [27].…”
Section: Multilayer Perceptron Artificial Neural Network (Mlp-ann)mentioning
confidence: 99%
“…It consists of three or more layers ( i.e., input and an output layer with one or more hidden layers) of nonlinearlyactivating nodes. This algorithm employs the backpropagation supervised learning method and works through determining the most proper synaptic weight in classifying patterns in the training dataset [27].…”
Section: Multilayer Perceptron Artificial Neural Network (Mlp-ann)mentioning
confidence: 99%
“…In [9] In [4] Ammar Odeh et al designed a Multi-Layer Perceptron by considering the URL features. On the extracted features, performed selection, combination of ranking and single attribute evaluation is performed.…”
Section: Related Workmentioning
confidence: 99%
“…Jain et al (2011) publication assessed the problem with remaining silent especially on the issues related to the project being developed. This empirical study conducted reviewed the prior research, which suggested that there is no communication between the client managers and the vendor's employees and this can lead to poor quality services that are offered to clients (Goby, 2015;Hossain et al, 2009;Odeh et al, 2020). Cross-cultural teams are also facing the challenge of understanding the views and demands of the employees and this can sometimes result to conflict in the decision-making process.…”
Section: A Rq1 -Barriers Identified Using Slrmentioning
confidence: 99%